Cardioprotective effect of vitamin D and melatonin on doxorubicin-induced cardiotoxicity in rat model: an electrocardiographic, scintigraphic and biochemical study - Gül, Serdar Savaş; Aygün, Hatice (The European Research Journal, 2019)
Objectives: Doxorubicin (DOX) is an antineoplastic drug that is widely used in chemotherapy but its cardiotoxicity is the most important side effect that limits the clinical use of this drug. We investigated DOX treatment and the effects of vitamin D and melatonin on heart by electrocardiography, scintigraphic and biochemical methods.Methods: In this study, forty-nine adult male Wistar albino rats (220 ± 15 g) were randomly divided into seven groups (n  =  7 each), namely control (CON, n = 7), doxorubicin (DOX, n = 7), melatonin (MEL, n = 7), vitamin D (Vit D, n = 7), doxorubicin plus melatonin (DOX+MEL, n = 7), doxorubicin plus vitamin D (DOX+Vit D, n = 7), and doxorubicin plus melatonin and vitamin D (DOX+MEL+Vit D, n = 7) groups. Cardiotoxicity was induced by intraperitoneal injection (i.p.) of DOX (18 mg/kg, i.p.) on the 15th, 16th and 17th days. Rats receiving vitamin D and melatonin treatment in the DOX-induced cardiotoxicity group received vitamin D (60,000 IU/kg, i.p.) were administered in a single dose and melatonin (40 mg/kg/day, i.p.) for 17 days and were injected with (18 mg/kg, i.p.) on doxorubicin 15th, 16th, and 17th days. On the 18th day electrocardiography (ECG), 99mTechnetium pyrophosphate scintigraphy and biochemical parameters were assessed.Results: DOX caused changes in the ECG pattern, a significant decrease in heartbeat (p < 0.01), P wave (p < 0.001) and QRS complex durations (p < 0.001), R wave amplitude (p < 0.001); elevation in ST-segment (p < 0.001) and decrease in QT interval (p < 0,001),  and R-R interval durations (p < 0.001); increase in the serum levels of cardiac injury markers (CK, BUN, cardiac troponin T), (p < 0.01), and increased 99mTechnetium pyrophosphate uptake (p < 0.001) as compared to the CON group. MEL, Vit D and MEL+Vit D administration showed a same protective effect against DOX-induced altered ECG pattern. Pre-treatment with MEL, Vit D and MEL+Vit D significantly protected the heart from the toxic effect of DOX, by decreasing the levels of of cardiac injury markers (CK, BUN, cardiac troponin T) (p < 0.001) and decreased the elevated level of 99mTechnetium pyrophosphate uptake (p < 0.001). Conclusion: Vitamin D and melatonin treatment prevented all the parameters of DOX-induced cardiotoxicity in rats.